The Effect Of Linktree-Based Learning Media On Mathematical Literacy Skiills In Junior High School - Annanda Shofi Sulthoni; Wildan Hakim (CV. Samuel Manurung and Co, 2025)
Students often face difficulties in understanding mathematical concepts, which affects their mathematical literacy. One way to address this issue is by utilizing innovative learning media. This study investigates the effect of Linktree-based educational resources on the mathematical literacy of junior high school students. Learning media play a crucial role in enhancing students' comprehension and facilitating the overall learning experience, especially for complex or poorly understood material. The study employs a quantitative approach with an ex-post facto experimental method, involving class VIII students at Wahidiyah Junior High School in Bululawang. A sample of 11 students was selected from the population. Data collection involved a mathematical literacy test and a questionnaire to assess the use of Linktree learning media. The data were analyzed using a parametric statistical regression test. The results indicate that Linktree learning media significantly influences mathematical literacy, with an impact level of 4.45% and a regression equation of Ŷ = -9.932 + 1.697X. It is recommended that mathematics teachers receive training on the effective use of linktree, and in future studies, other researchers should use a larger sample size to gain deeper insights into its impact on mathematical literacy.